AKULTURASI BUDAYA JAWA DAN MELAYU PADA UPACARA PERNIKAHAN DI DESA SRI MENANTI KECAMATAN TANJUNG LAGO KABUPATEN BANYUASIN - Budi Aswar; Endang Rochmiatun; Sri Suriana (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 2021)
This research departs on the phenomenon of acculturation of Indonesian culture. Indonesia is famous for its cultural diversity. The cycle of life starting from birth, marriage and death are all regulated in culture. Marriage is an anthropological study that sees marriage as a culture. This study uses an anthropological approach and uses the redfied theory, namely acculturation. Furthermore, this study uses a qualitative descriptive method. The results of this discussion can be in several points. 1). Marriage is a sacred ritual in life, 2). The influence of social contact makes the acculturation process run well with some of the same values ​​of harmony, 3). Javanese and Malay weddings have differences in rituals although there are similarities and slightly different pronunciations. 4). Acculturation includes pre-wedding, wedding day and post-wedding.